The Spirit of the Law in the Thought of Reinhold Niebuhr - Rice, Daniel F. (Journal of law and religion, 1986)
Reinhold Niebuhr (1892-1971) possessed wide-ranging interests and a unique penchant for intellectual synthesis which understandably commended him to a far broader audience than is normally accorded theologians in this desacralized age. Niebuhr's orientation was theology and politics, and by his own admission, he saw himself working out of the context of Christian social ethics. Precisely because this was the framework of his labors, Niebuhr figured and continues to figure prominently among those persons whose interests center upon social, political, and ethical concerns so pertinent to the domain of law. Niebuhr neither fashioned himself a legal expert, nor did he conceive of himself as a legal theorist. Nonetheless, because of his standing in contemporary Protestantism, and because of his orientation as a theologian of social ethics, Niebuhr finds himself in the rather select circle of theologians who have something of note to say about the place of law in the affairs of humankind.Political theorist Hans Morgenthau called Niebuhr "the greatest living political philosopher of America, perhaps the only creative political philosopher since Calhoun." In this context, Gordon Harland makes the point that Niebuhr's "theological and political thought forms one consistent whole: and that there is a "vital organic relation between Niebuhr's social and political thought and the ultimate reaches of his theological reflections." It is because Niebuhr spoke with conviction out of the Biblical tradition that he was concerned about the relationship of love to law. And precisely because he spoke convincingly as a political realist, he was concerned with the relationship between justice and law. But in speaking as both theologian and political realist, Niebuhr's approach to the problem of law was articulated in terms of the dialectical relationship between love and justice.